Kewenangan Pemerintah Pusat Melalui Menteri Hukum dan HAM Dalam Mengevaluasi Peraturan Perundang-undangan - Budi Santho Parulian Nababan; Faisal Akbar; Afnila Afnila; Mirza Nasution (Universitas Sumatera Utara, 2019)
Abstract. The State of Indonesia is a state of law that cannot be separated from the regulations so that many regulations are produced, but there are conflicts, multiple interpretations, inconsistencies, and not operational, so that President Joko Widodo issues a legal revitalization policy package throught the regulation structuring program, institutional reform, and legal culture development. One of the sub programs on structuring regulations is the evaluation regulations by the Minister of Law and Human Rights. Since 2016 The Minister of Law and Human Rights has evaluated 759 legislations central with detail: in 2016 there were 193 legislation; in 2017 there were 295 laws and regulations; and in 2018 there will be 271 laws and regulation, but the results of the evaluation regulations by The Minister of Law and Human Rights don’t yet have a binding capacity for the ministries/institutions mentioned in the recommendations and don’t yet have a legal umbrella that requires the recommendations to be followed Keywords: minister of law and human rights, regulations, evaluation of regulations